UPAYA MENINGKATKAN HASIL BELAJAR KOGNITIF BAHASA INDONESIA SISWA KELAS VIII-A MELALUI PENERAPAN MODEL PEMBELAJARAN STAD SMP NEGERI 1 PANYABUNGAN SELATAN - Habibah Habibah (Universitas Negeri Medan, 2017)
Abstract: Efforts to Improve Learning Outcomes of Indonesian Students' Cognitive Learning of Class VIII-A Through Application of Learning Model of STAD SMP Negeri 1 Panyabungan Selatan. This study aims to determine students' cognitive learning outcomes and student learning activities. Research subjects amounted to 35 people. Based on the findings of student learning outcomes cycle I only 17 people graduated KKM or complete class that is 49%. Formative data II shows 31 students complete the individual or 88% in classical. The data of both observers showed an increase in student learning activity on the activities of doing LKS and Ask friends. Cycle I Data Writing / reading activity (42%), LKS work activity (26.5%), asked friends (16.5%), teacher asked activity (11.5%). Activities not in accordance with the KBM is still at (3.5%). The data of cycle II shows the activity of doing LKS (45,5%), writing / reading (21,5%), Asking friend (20,5%), activity ask teacher reach proportion (12%), and activity not relevant with KBM is (0.5%). Keywords: STAD Learning Model, Learning Outcomes, Learning Activity Abstrak : Upaya Meningkatkan Hasil Belajar Kognitif Bahasa Indonesia Siswa Kelas VIII-A Melalui Penerapan Model Pembelajaran STAD SMP Negeri 1 Panyabungan Selatan. Penelitian ini bertujuan untuk mengetahui hasil belajar kognitif siswa dan aktivitas belajar siswa. Subjek penelitian berjumlah 35 orang. Berdasarkan temuan hasil belajar siswa siklus I hanya 17 orang lulus KKM atau ketuntas kelas yaitu 49%. Data formatif II menunjukan 31 siswa tuntas individu atau 88% secara klasikal. Data kedua pengamat menunjukan peningkatan aktivitas belajar siswa pada aktivitas mengerjakan LKS dan Bertanya pada teman. Data siklus I Aktivitas menulis/membaca (42%), aktivitas mengerjakan LKS (26,5%), bertanya kepada teman (16,5%), aktivitas bertanya pada guru sebesar (11,5%). Aktivitas yang tidak sesuai dengan KBM masih sebesar (3,5%). Data siklus II menunjukan aktivitas mengerjakan LKS (45,5%), menulis/membaca (21,5%), Bertanya pada teman (20,5%), aktivitas bertanya pada guru mencapai proporsi (12%), dan aktivitas tidak relevan dengan KBM yaitu (0,5%). Kata Kunci : Model Pembelajaran STAD, Hasil Belajar, Aktivitas Belajar